Composition, antioxidant capacity and quality of yellow passion fruit during storage - Rotili, Maria Cristina Copello; Coutro, Sidiane; Celant, Viviane Marcela; Vorpagel, Jessica Ariane; Barp, Fabiane Karine; Salibe, Ariane Busch; Braga, Gilberto Costa (Semina: Ciências Agrárias, 2013)
In this work, the contents of phenolic compounds, B-carotene, ascorbic acid and antioxidant activity (DPPH and TEAC methods) were determined in the yellow passion fruit juice during storage at 5 and 24 Â° C, at intervals of 10 days. The fruit quality during storage was determined, and the parameters weight loss, wrinkles, skin color and pathogenic degradation index were used. Samples of fruit at maturity stage with the skin color predominantly green were used for the tests. The results showed that total phenolic compounds, B-carotene and antioxidant activity of the yellow passion fruit juice were not affected by storage temperature and the content of total phenolic compounds of the juice increased with storage time. It as demonstrated that the effects of high temperature during storage is much more evident and impacting the appearance of the fruit, which in the nutritional quality of the juice. The antioxidant activity of juice, expressed in kidnapping DPPH decreased during storage. Based on the microbiological quality, the shelf life of yellow passion fruit was extended to 20 days in refrigerated storage.